2020
DOI: 10.3390/biology9110398
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Splicing Factor 1 (SF1) Reduces Intestinal Polyp Incidence in ApcMin/+ Mice

Abstract: Background: Splicing factor 1 (SF1) is a conserved alternative splicing factor expressed in many different mammalian cell types. The genetically modified Sf1+/− (or Sf1β-geo/+) mice express reduced levels of SF1 protein in mouse tissues, including in cells of the intestines. Mutational inactivation of human adenomatous polyposis coli (APC) gene deregulates the Wnt signaling pathway and is a frequent genetic event in colon cancers. Mice with a point mutation in the Apc gene (ApcMin/+) also develop numerous inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Alternative signals may change a protein's structure or function within the cell. Thus, the wide variety of proteins that may precisely tailor cellular function to the condition of the cells' biology is produced through alternative splicing [ 40 ]. It has been reported that SF1 is associated with aging.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative signals may change a protein's structure or function within the cell. Thus, the wide variety of proteins that may precisely tailor cellular function to the condition of the cells' biology is produced through alternative splicing [ 40 ]. It has been reported that SF1 is associated with aging.…”
Section: Discussionmentioning
confidence: 99%